2011
DOI: 10.1002/aoc.1795
|View full text |Cite
|
Sign up to set email alerts
|

A Suzuki‐type cross‐coupling reaction of arylacetylene halides with arylboronic acids

Abstract: A PdCl 2 -catalyzed direct alkynylation of arylboronic acids to give diarylacetylenes is described. The optimal conditions using PdCl 2 as catalyst, MeOH-PhMe-H 2 O as solvent and K 2 CO 3 as base effectively suppressed the formation of homo-coupling product and afforded moderate to good yield of the desired unsymmetrical coupling product. This reaction represents a Suzuki-type sp 2 (C-B)-sp(C-X) cross-coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Although some reactions proceeded under relatively mild conditions to afford the corresponding internal alkynes, these reactions required a large amount of amine bases, such as pyridine or lutidine. On another front, Suzuki–Miyaura‐type reactions of arylboronic acids with bromoalkynes have been reported as another synthetic protocol for the preparation of internal alkyne derivatives . In this reaction, the Pd catalyst worked well and promoted the reaction under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some reactions proceeded under relatively mild conditions to afford the corresponding internal alkynes, these reactions required a large amount of amine bases, such as pyridine or lutidine. On another front, Suzuki–Miyaura‐type reactions of arylboronic acids with bromoalkynes have been reported as another synthetic protocol for the preparation of internal alkyne derivatives . In this reaction, the Pd catalyst worked well and promoted the reaction under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this reaction, the Pd catalyst worked well and promoted the reaction under mild conditions. [15c] Furthermore, Wang et al have reported a Cu‐catalyzed Suzuki–Miyaura‐type reaction of bromoalkyne with arylboronic acid to produce an internal alkyne derivative . Although this reaction has the potential to become an effective method for the synthesis of o ‐allyloxy(ethynyl)benzene, it also requires reflux conditions.…”
Section: Introductionmentioning
confidence: 99%